Temporal changes in the wolf Canis lupus diet in Wigry National Park (northeast Poland). Issue 6 (2nd November 2021) - Mysłajek, Robert W.; Romański, Maciej; Kwiatkowska, Iga; Stępniak, Kinga M.; Figura, Michał; Nowak-Brzezińska, Agnieszka; Diserens, Tom A.; Nowak, Sabina
Abstract : Earlier studies have indicated that consumption of beavers Castor ssp. by wolves Canis lupus varies seasonally and is influenced by rainfall affecting water levels. Therefore, to determine whether these carnivores prey more often on beavers in drier seasons and years, we assessed the diet of wolves in Wigry National Park (NE Poland) by analysing 303 scats collected from 2017 to 2019. The most important prey of wolves in this region was the wild boar Sus scrofa (25.2% of consumed biomass), Eurasian beaver Castor fiber (24.4%) and roe deer Capreolus capreolus (24.2%). Predator niche breadth was broader in spring-summer (B = 2.24) than in autumn-winter (B = 1.32), mainly due to higher consumption of beavers (37.3% in spring-summer and 10.7% in autumn-winter). Wolves consumed more beavers (40.9%) and had the broadest niche breadth (B = 1.99) in 2019, when the annual rainfall was lowest. Our study provides further evidence that wolves prey on beavers more often in ice-free seasons and drier years.